EFEKTIVITAS METODE SHOW AND TELL DALAM MENDUKUNG PERKEMBANGAN BAHASA ANAK USIA DINI - Munawwarah Samad; Nazrah Lutfia Putri; Heliati Fajriah (Bunayya, 2026)
Based on the results of observations that have been made in Kindergarten, there are problems that occur in children aged 5-6 years, where the development of children's language is still weak, it can be seen that children are not able to communicate orally, answering the other people's questions, the words issued are stammered and are not able to convey ideas, as well as lack of vocabulary. The purpose of this study is to determine whether the use of the show-and-tell method can support children's language development at Cut Nyakti Blanggeulingang Kindergarten. This study uses a quantitative method of experimental type with a quasi-pretest-postest non-quivalent control group design. This design consists of an experimental group and a control group. The results obtained from the ttable > tcount values were 7.670 > 1.691, thus there was a rejection of Ho and acceptance of Ha, which means that there was an influence of the application of the show and tell method on language development in children aged 5-6 years at Cut Nyakti Blanggeulinggang Kindergarten.